PWE-421 Knowledge of refeeding syndrome amongst foundation year doctors. (22nd June 2015) - On, W; Harrison, R; Haddick, A
Abstract : Introduction: Refeeding syndrome (RS) is a potentially fatal condition and our trust has local guidelines in place to monitor for RS. Junior doctors on the wards are often the ones who are most responsible for the day-to-day care of patients and thus, they should be aware of the risk factors, monitoring and treatment of RS. We aimed to assess the knowledge of RS amongst Foundation Year 1 (F1) and Year 2 (F2) doctors in our trust. Method: We conducted a paper questionnaire survey which was distributed to F1s and F2s over a time period from October 2014 to December 2014. The contents of the survey were based off the 2006 NICE guidelines 'Nutrition support in adults' 1 and our trust's local guidelines. Results: The response rate was 56% (55/99). All respondents were aware of RS. 49% were able to list 2 risk factors for RS. 69% were aware of which electrolytes that were of importance in the monitoring of RS and 91% would monitor the electrolytes daily until stable. Only 40% were aware of the importance of supplementary vitamins such as thiamine, vitamin B co-strong and multivitamin in patients at risk of RS. 7% were able to list 3 clinical complications of RS. Only 26% were aware of our trust's guidelines on RS. Conclusion: Our survey showed that whilst junior doctors were aware of RS, the knowledge of management of RS in clinical practice has to be improved upon. Further education is needed and junior doctors should be aware of the availability of national and local trust guidelines which are valuable resources. Disclosure of interest: None Declared. Reference: NICE CG32 Guidelines: Nutrition support in adults. (http://www.nice.org.uk/guidance/cg32/ )